Multicenter Study of Congenital Middle Ear Anomalies. Report on 246 Ears. (1st March 2021) - Ito, Tsukasa; Furukawa, Takatoshi; Ohshima, Shinsuke; Takahashi, Kuniyuki; Takata, Yusuke; Furukawa, Masayuki; Hiraumi, Harukazu; Yamauchi, Daisuke; Yuasa, Yu; Goto, Shinichi; Sasaki, Akira; Koizumi, Koh; et al.
Abstract : Objectives/Hypothesis: Congenital middle ear anomalies represent a relatively rare condition. This study aimed to describe the characteristics and the surgical outcomes for patients with middle ear anomalies. Methods: A multicenter study was conducted of consecutive patients with congenital middle ear anomalies who underwent primary surgical treatment between January 2008 and December 2017. Demographics, surgical procedures, and audiometric data were registered into the institutional database. Hearing changes and postoperative air‐bone gap (ABG) were evaluated 1 year after surgery. Results: A total of 246 patients (246 ears) (median age: 14 years, range: 4–75 years old) were included in this study. Anomalies were subdivided using the Teunissen and Cremers classification: 53 ears (22%) were categorized as class I, comprising only stapes ankylosis; 35 ears (14%) as class II, having ossicular chain anomalies with stapes ankylosis; 139 ears (57%) as class III, having ossicular chain anomalies with a mobile stapes‐footplate; and 19 ears (8%) as class IV, with aplasia of the oval window. Evaluation of hearing outcomes for 198 ears with more than 1 year of follow‐up revealed that good postoperative ABG (≤20 dB) was achieved in 82% of class I, 68% of class II, 74% of class III, and 23% of class IV anomalies. The postoperative ABG in class IV was significantly worse than in class I ( P  < .001) or class III ( P  < .01). Conclusions: This study demonstrated that class III anomalies comprised the majority of middle ear anomalies and surgical outcomes for class IV anomalies are unfavorable. Level of Evidence: 4 Laryngoscope, 131:E2323–E2328, 2021